The economics of the stock market - West, Richard R.; Tiniç, Seha M. (New York : Praeger, 1971)
This book is about the market for corporate common stock. Unlike most books on the stock market, this one does not focus primarily on the forces influencing the supply of common shares or their demand by various investor groups.
Includes bibliographies.
osc 9/11/17
Loans
Keywords: Stock exchanges; Stocks